2008
DOI: 10.1590/s0103-90162008000400002
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and productive responses of environmental control on housed sows

Abstract: Swine housing must promote an adjusted environment for thermal comfort and high animal productivity without negatively affecting the sow performance and reproductive response. This study evaluated the use of distinct environmental cooling equipments on sow performance, both on the gestation and on nursing in open sided housing. Two treatments were tested in the gestation building: natural ventilation and mechanical ventilation associated to fogging; while in the nursing rooms three treatments were tested: natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…The condition was evaluated by means of backfat thickness and/or weight loss percentage during lactation. ROMANINI et al (2008) reported higher backfat thickness in sows submitted to treatment with evaporative cooling. With regard to weight loss, KIEFER et al (2012) observed lower weight loss in sows submitted to cooling (<8%) ( Table 6).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The condition was evaluated by means of backfat thickness and/or weight loss percentage during lactation. ROMANINI et al (2008) reported higher backfat thickness in sows submitted to treatment with evaporative cooling. With regard to weight loss, KIEFER et al (2012) observed lower weight loss in sows submitted to cooling (<8%) ( Table 6).…”
Section: Resultsmentioning
confidence: 91%
“…With the review, it was observed that the feed intake was improved when using the cooling system, agreeing with those of body condition in which the use of cooling allowed smaller losses. ROMANINI et al (2008) demonstrated that sows submitted to forced ventilation or evaporative cooling showed a greater backfat thickness (14.9 mm) relative to natural ventilation (14.5 mm).…”
Section: Discussionmentioning
confidence: 98%
“…An evaporative-cooling pads system is often used to decrease the air-stream temperature in zone-cooling technology [ 6 , 10 , 64 , 65 ]. Justino et al [ 6 ] used air of velocity above 3 m/s, cooled by an evaporative-pad system, distributed around group of lactating sows (through plastic ducts with holes in it).…”
Section: Cooling Technologiesmentioning
confidence: 99%
“…Zone-cooling technology associated with evaporative pads was tested also in terms of improving the performance indicators of sows [ 10 , 64 ]. For example, the effectiveness of the evaporative snout-cooling method with a traditional temperature control system (curtain management) on, among others, piglet body weight has been compared [ 10 ].…”
Section: Cooling Technologiesmentioning
confidence: 99%
See 1 more Smart Citation